The Influence of Intended Strategy and Emergent Strategy on Open Innovation in Improving the Performance of the Creative Economy Industry in Sounth Sumatra and West Sumatra - Arfah Piliang; Nuraini Nuraini; Rasmon Rasmon; Candra Irawan; Jonnedi Jonnedi; Supriatiningsih Supriatiningsih (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This study investigates how both planned (intended) and adaptive (emergent) strategies influence the adoption of open innovation and examines their subsequent effects on the performance of creative industries in South and West Sumatra. Employing a quantitative survey of 150 industry participants, the findings reveal that each strategy positively contributes to the implementation of open innovation. Moreover, open innovation acts as a mediating mechanism that enhances business performance. These outcomes underscore the importance of integrating deliberate planning with agile responses to strengthen innovation capabilities and drive organizational success within the creative economy